2023
DOI: 10.3390/ijerph20021156
|View full text |Cite
|
Sign up to set email alerts
|

“How Do I Exist in This Body…That’s Outside of the Norm?” Trans and Nonbinary Experiences of Conformity, Coping, and Connection in Atypical Anorexia

Abstract: Addressing eating disorders (EDs) within trans and nonbinary (TNB) populations is a growing concern, as TNB individuals are two to four times more likely to experience EDs than cisgender women. This study explored the lived experiences of TNB people with atypical anorexia by examining how gender identity impacted experiences of ED illness and (potential) recovery. Nine TNB adults with atypical anorexia were followed for one year and completed semi-structured, in-depth, longitudinal qualitative interviews at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Disordered eating, particularly food restriction, may be a strategy of dealing with gender dysphoria and a changing body [46,47,48 ▪ ]. In a qualitative study of gender diverse people living with eating disorders, participants explained that their eating disorders represented attempts to cope with body dissatisfaction, gender dysphoria, and feeling disconnected from the body [48 ▪ ]. Experiences of discrimination and pressures from gender norms around thinness, fatness, and muscularity were major contributors to their body dissatisfaction and gender dysphoria [48 ▪ ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Disordered eating, particularly food restriction, may be a strategy of dealing with gender dysphoria and a changing body [46,47,48 ▪ ]. In a qualitative study of gender diverse people living with eating disorders, participants explained that their eating disorders represented attempts to cope with body dissatisfaction, gender dysphoria, and feeling disconnected from the body [48 ▪ ]. Experiences of discrimination and pressures from gender norms around thinness, fatness, and muscularity were major contributors to their body dissatisfaction and gender dysphoria [48 ▪ ].…”
Section: Methodsmentioning
confidence: 99%
“…In a qualitative study of gender diverse people living with eating disorders, participants explained that their eating disorders represented attempts to cope with body dissatisfaction, gender dysphoria, and feeling disconnected from the body [48 ▪ ]. Experiences of discrimination and pressures from gender norms around thinness, fatness, and muscularity were major contributors to their body dissatisfaction and gender dysphoria [48 ▪ ]. Some participants also attempted to meet the weight requirements of gender-affirming surgery by focusing on their weight in an unhealthy way [48 ▪ ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, many trans men and non-binary people assigned female at birth (AFAB) are denied chest masculinization surgery due to BMI limits set by surgeons ( 5 ). When considerations such as these are not accounted for, nutritional care—particularly eating disorders treatment—may be less effective or even iatrogenic ( 6 ). In fact, several qualitative studies have reported that the efficacy and acceptability of gender-diverse participants' eating disorders treatment experiences hinged on whether their gender identity was considered during recovery [e.g., ( 3 )].…”
Section: Introductionmentioning
confidence: 99%